Comprehensive analysis of regional disparities in the distribution of income and welfare of the population in the Russian regions - V. V. Stroev (Вестник университета)
The modern Russian economy is characterised by considerable regional disparities concerning distribution of incomes and well-being of the citizens. These imbalances can be especially noticeable when analysing various sectors which play an important role in the economic progress of the regions. Within the framework of this study, based on a comparative analysis, the degree of dependence of the living standard on the electromechanical industry is assessed. The hypothesis is advanced that the outstripping growth of this sector has a significant positive impact on indicators of employment, income, and quality of life. Testing this hypothesis will make it possible to create a state policy for equalising the socio-economic development of Russian regions with consideration to the industry specialisation of their economies. Statistical data on personal income, quality of life indices, as well as specific indicators of industry progress in different regions of the Federation were used for the study. The employed methods of correlation and regression analysis identified the links between the level of sectoral development and economic well-being of the territorial units. The analysis showed that such regions as Moscow, St. Petersburg, where an infrastructure sector leads, and a number of oil-producing Siberian regions demonstrate higher indicators of income and quality of life. At the same time, subjects with a less developed sector, for instance some areas of the North Caucasus and Siberia, are experiencing difficulties in achieving similar levels of welfare.